Phase II Trial of the CDK4 Inhibitor PD0332991 in Patients With Advanced CDK4-Amplified Well-Differentiated or Dedifferentiated Liposarcoma - Dickson, Mark A. (American Society of Clinical Oncology, 2013)
PURPOSE: CDK4 is amplified in > 90% of well-differentiated (WDLS) and dedifferentiated liposarcomas (DDLS). The selective cyclin-dependent kinase 4 (CDK4)/CDK6 inhibitor PD0332991 inhibits growth and induces senescence in cell lines and xenografts. In a phase I trial of PD0332991, several patients with WDLS or DDLS experienced prolonged stable disease. We performed an open-label phase II study to determine the safety and efficacy of PD0332991 in patients with advanced WDLS/DDLS. PATIENTS AND METHODS: Patients age ≥ 18 years experiencing disease progression while receiving systemic therapy before enrollment received PD0332991 200 mg orally once per day for 14 consecutive days in 21-day cycles. All were required to have CDK4 amplification by fluorescence in situ hybridization and retinoblastoma protein (RB) expression by immunohistochemistry (≥ 1+). The primary end point was progression-free survival (PFS) at 12 weeks, with 12-week PFS of ≥ 40% considered promising and ≤ 20% not promising. If ≥ nine of 28 patients were progression free at 12 weeks, PD0332991 would be considered active. RESULTS: We screened 48 patients (44 of 48 had CDK4 amplification; 41 of 44 were RB positive). Of those, 30 were enrolled, and 29 were evaluable for the primary end point. Grade 3 to 4 events included anemia (17%), thrombocytopenia (30%), neutropenia (50%), and febrile neutropenia (3%). At 12 weeks, PFS was 66% (90% CI, 51% to 100%), significantly exceeding the primary end point. The median PFS was 18 weeks. There was one partial response. CONCLUSION: Treatment with the CDK4 inhibitor PD0332991 was associated with a favorable progression-free rate in patients with CDK4-amplified and RB-expressing WDLS/DDLS who had progressive disease despite systemic therapy.